Interdisciplinary Learning of Low-Code Development Platform Programming with Dual Coding Theory-A Case Study of Agilepoint NX - Chung-Hsiang Wang; Ko-Chiu Wu (Journal of ICT, Design, Engineering and Technological Science, 2022)
This paper studies the interdisciplinary learning process of programming and computational thinking by design students trying to use a cloud-based low-code development platform with an information visualization interface. We researched and set up an 8-week “AgilePoint NX” programming course, which guided students with the introduction of computational thinking and learned from dual coding theory. In image process and low-code learning, we can carry out structured thinking and problem thinking and complete project tasks practice. We comprehensively analyze and evaluate their learning effectiveness through classroom learning observation, student sampling, brief interviews, and feedback. Finally, it is found that students from different backgrounds have different cognitive learning effects on interdisciplinary learning programs. Different factors on learning pain points lead to students’ low learning of programming courses. Exploring their learning process can be used as a reference for interdisciplinary learning and low-code development platform programming.